Daily activity of sumatran tiger (Panthera tigris sumatrae) and bengal tiger (Panthera tigris tigris) in Bali Zoo, Gianyar - Dewi, Putu Laksmi Candra; Yuni, Luh Putu Eswaryanti Kusuma; Watiniasih, Ni Luh (Jurnal Biologi Udayana, 2021)
Bali Zoo is an ex-situ conservation institution for various species of animals, including the bengal tiger and the sumatran tiger. Both species are included in the IUCN list with endangered status for the bengal tiger and critical status for the sumatran tiger. This study aimed to determine the daily activities of the two species of tigers at the Bali Zoo. Daily activity data collection was conducted by using focal animal sampling method, recording activities was conducted by using the instantaneous recording method on 30 second time interval within 30 minutes. The data collection was undertaken in morning, midday, and afternoon. Both tiger species allocated most of their time for resting. Sumatran tigers allocated 64,69 ± 2,52% of their time for resting, 31,32 ± 2,46% for moving, 2,72 ± 0,40% for grooming, 0,37 ± 0,08% for urinating 0,33 ± 0.11% for eating, 0,31 ± 0,07% for drinking, and 0,26 ± 0,08% for social activities. For the bengal tigers, they allocated 68,23 ± 2,20% of their time for resting, 24,14 ± 1,99% for moving, 3,54 ± 0,34% for social activities, 2,23 ± 0,29% for grooming, 0,39 ± 0,08% for urinating, 0,39 ± 0,09% for drinking, and 0,08 ± 0,18% for eating. Very low proportion of pacing activity was recorded in both species in which indicated that they felt comfortable in their captivity.